ON THE NUMBER OF SERVED CUSTOMERS IN $BMAP(t)|G|∞$ MODEL - Khajkhnidi, A. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In the present paper the $BMAP(t)|G|∞$ model with non-stationary input stream of customers is considered. The distribution of customers’ number served during time t and its mean value are obtained. Estimates for characteristics of $MAP(t)|G|∞$ and $M^x(t)|G|∞$ models are obtained as well.
Keywords: queuing model; MAP stream; infinite number of servers